MATHEMATICAL BASES DECISION OF OLYMPIAD TASKS FROM INFORMATICS ON SITE E-OLIMP - Vakalyuk, T.A. (Journal of Information Technologies in Education (ITE), 2010)
In the article a new section is examined on a portal from the sporting programming of e-olimp, namely mathematical bases during uniting of olympiads them tasks from an informatics.